Effect of dilute acid pretreatment on the saccharification and fermentation of rye straw. (28th February 2019) - Robak, Katarzyna; Balcerek, Maria; Dziekońska‐Kubczak, Urszula; Dziugan, Piotr
Abstract : This research shows the effect of dilute acid pretreatment with various sulfuric acid concentrations (0.5–2.0% [wt/vol]) on enzymatic saccharification and fermentation yield of rye straw. After pretreatment, solids of rye straw were suspended in Na citrate buffer or post‐pretreatment liquids (prehydrolysates) containing sugars liberated after hemicellulose hydrolysis. Saccharification was conducted using enzymes dosage of 15 or 25 FPU/g cellulose. Cellulose saccharification rate after rye straw pretreatment was enhanced by performing enzymatic hydrolysis in sodium citrate buffer in comparison with hemicellulose prehydrolysate. The maximum cellulose saccharification rate (69%) was reached in sodium citrate buffer (biomass pretreated with 2.0% [wt/vol] H2 SO4 ). Lignocellulosic complex of rye straw after pretreatment was subjected to separate hydrolysis and fermentation (SHF) or separate hydrolysis and co‐fermentation (SHCF). The SHF processes conducted in the sodium citrate buffer using monoculture of Saccharomyces cerevisiae (Ethanol Red) were more efficient compared to hemicellulose prehydrolysate in respect with ethanol yields. Maximum fermentation efficiency of SHF processes obtained after rye straw pretreatment at 1.5% [wt/vol] H2 SO4 and saccharification using enzymes dosage of 25 FPU/g in sodium citrate buffer, achieving 40.6% of theoretical yield. However, SHCF process using cocultures of pentose‐fermenting yeast, after pretreatment of raw material at 1.5% [wt/vol] H2 SO4 and hydrolysis using enzymes dosage of 25 FPU/g, resulted in the highest ethanol yield among studied methods, achieving 9.4 g/L of ethanol, corresponding to 55% of theoretical yield.